Non-stimulated, agonist-stimulated and store-operated Ca2+ influx in MDA-MB-468 breast cancer cells and the effect of EGF-induced EMT on calcium entry. - Felicity M Davis; Amelia A Peters; Desma M Grice; Peter J Cabot; Marie-Odile Parat; Sarah J Roberts-Thomson; Gregory R Monteith (PLoS ONE, 2012)
In addition to their well-defined roles in replenishing depleted endoplasmic reticulum (ER) Ca(2+) reserves, molecular components of the store-operated Ca(2+) entry pathway regulate breast cancer metastasis. A process implicated in cancer metastasis that describes the conversion to a more invasive phenotype is epithelial-mesenchymal transition (EMT). In this study we show that EGF-induced EMT in MDA-MB-468 breast cancer cells is associated with a reduction in agonist-stimulated and store-operated Ca(2+) influx, and that MDA-MB-468 cells prior to EMT induction have a high level of non-stimulated Ca(2+) influx. The potential roles for specific Ca(2+) channels in these pathways were assessed by siRNA-mediated silencing of ORAI1 and transient receptor potential canonical type 1 (TRPC1) channels in MDA-MB-468 breast cancer cells. Non-stimulated, agonist-stimulated and store-operated Ca(2+) influx were significantly inhibited with ORAI1 silencing. TRPC1 knockdown attenuated non-stimulated Ca(2+) influx in a manner dependent on Ca(2+) influx via ORAI1. TRPC1 silencing was also associated with reduced ERK1/2 phosphorylation and changes in the rate of Ca(2+) release from the ER associated with the inhibition of the sarco/endoplasmic reticulum Ca(2+)-ATPase (time to peak [Ca(2+)](CYT) = 188.7 ± 34.6 s (TRPC1 siRNA) versus 124.0 ± 9.5 s (non-targeting siRNA); P<0.05). These studies indicate that EMT in MDA-MB-468 breast cancer cells is associated with a pronounced remodeling of Ca(2+) influx, which may be due to altered ORAI1 and/or TRPC1 channel function. Our findings also suggest that TRPC1 channels in MDA-MB-468 cells contribute to ORAI1-mediated Ca(2+) influx in non-stimulated cells.